Studi Kajian Garis Kemiskinan dan Penduduk Miskin di Kabupaten Deli Serdang - Pipit Yuspira; Igk Adhi Sugara; Rizky Pramudita Bukit; Edi Suprayetno; Dewi Mahrani Rangkuty (Universitas Katolik Widya Karya Malang, 2023)
Poverty is a central issue for every country worldwide, especially developing countries such as Indonesia. Some factors that cause poverty include low local and global economic growth, low levels of education and mastery of technology, limited natural resources, and high population growth. This study aims to look at the percentage of poor people and the poverty line in Deli Serdang. This study is a qualitative descriptive method with literature and literature studies from journals of previous research results. In 2022, Deli Serdang Regency was found to be the Regency with the smallest poverty percentage value in North Sumatra Province.